BS EN ISO 15213-1. Microbiology of the food chain. Horizontal method for the detection and enumeration of Clostridium spp. Part 1. Enumeration of sulfite-reducing Clostridium spp. by colony-count technique (15th September 2021) - British Standards Institution,
No abstract available